PHYSICO-CHEMICAL PROPERTIES OF BIODIESEL DERIVED FROM LANNEA MICROCARPA OIL: A COMPARATIVE ANALYSIS WITH FOSSIL DIESEL - Wada, Ibrahim; Yahaya, Dalhatu Balarabe; Garba, Isa (FUDMA Journal of Sciences, 2025)
In the present study, non-edible oil of Lannea microcarpa was extracted through the use of a mechanical press and biodiesel was produced from the extracted oil in two steps reactions of esterification and alkali-catalyzed trans-esterification. The percentage oil and biodiesel yield were found to be 46.15% and 90.63%wt respectively. The physico-chemical properties of the biodiesels were investigated and comparatively analysed to ascertain the suitability of this biodiesel to replace fossil diesel. The physico-chemical properties evaluated were also compared with reported values in the literature. The results showed that L. microcarpa biodiesel had density (0.8965g/cm3), kinematics viscosity  (6.00 mm2/s), cetane number (41.98),  flash point  (1280C), fire point  (1400C), calorific value  (38.5 MJ/kg), cloud point  (50C), pour point (-9.50C), iodine value  (120gI/100g),  saponification value (240mgKOH/g), carbon residue (0.50%) and ash content (0.03%). It was revealed that, seven out of the twelve assessed properties conformed to ASTM standard but iodine value, calorific value, cetane number, carbon residue and ash content deviated slightly with negligible differences. It was also noted that, the density, viscosity, cetane number, calorific value, ash content and carbon residue of fossil diesel were found to be slightly better than those of the biodiesel. Conversely, the biodiesel exhibited slightly better cloud point, pour point, flash point, and fire point than fossil diesel. Hence, Lannea microcarpa biodiesel considered to met the specified standard recommendations for suitably used in conventional diesel engines.
Keywords: Lannea microcarpa seed oil; Biodiesel; Physio-chemical properties; ASTM; Diesel